Design and implementation of a digital front-end for multi-standard software defined radio receiver - Munusamy, Puvaneswari; Sidek, Othman (Penerbit Universiti Sains Malaysia, 2004)
Software defined radio (SDR) is an emerging technology, thought to realize flexible radio systems, multi-service, multistandard, re-configurable and reprogrammable by software (Buracchini,2000). A goal in SDR is to push the digitization point as close as possible to the antenna (Hentschel et. al.,1999).